THE BUDGET CALCULATION WITH TWO-PHASE REGRESSION TO ESTIMATE THE AFFORDABLE COSTS OF EDUCATION IN SERANG CITY - Suherman, .; Ardi, Romli; Muhyidin, Asep; Juansah, Dase Erwin; Widiastuti, Sri (PEOPLE: International Journal of Social Sciences, 2016)
In the era of regional autonomy, the costs of basic education is the responsibility of the district/city. The dominant factors that triggered the education expenses consist of teacher salaries, employer salaries, material and operational costs, and administrative costs. The calculation of basic education costs in this study is focusing on all Junior High School (SMP) in Serang city, as many as 56 schools, consisting of 23 public schools and 33 private schools. This study began with the budget review to estimate the SchoolBudget Plan (RAPBS). It was conducted with the aim to estimate the costs of education over the next five years. Estimated costs werecalculated by the method of regression trend exponentially through two phases. To achieve these objectives, the empirical method was used with survey approach. Based on a review of all RAPBS, every component in every school has a different fee scale. The results of budget estimation for junior high schools in Serang City are in the range of Rp.6.131.250.000- Rp.6.699.240.000; with a unit cost of education per student per year is Rp.455.556-Rp.517.378.